Making Size and Democracy Multidimensional: Beyond the Gap between Capacity and Proximity. - Bolgherini, Silvia; Casula, Mattia; Marotta, Mariano (Taylor & Francis, 2019)
In recent decades, several studies have focused on the impact of rescaling processes on local democracy, investigating whether and how size, performance and citizens' preferences are taken into account by local administrators when approaching these processes. Taking the longstanding dilemma between systemic capacity and democratic proximity as its starting point, this paper fits into this debate by adopting a multidimensional approach to further investigate municipal rescaling and its implications. A set of original variables and indicators to address the tradeoff between capacity and proximity will be presented and empirically applied to the Italian case. Along with the collection of new data and some ideas for applied rescaling, the paper suggests several dimensions of analysis suitable for comparative studies on municipal rescaling and planning. The findings partially confirm the existing literature on some consolidated variables but also suggest, through the new variables proposed here, that both the municipal size and the position/location of the municipality within the area involved in rescaling be considered in a more articulated way. A threefold contribution is thus provided: theoretically, by assessing the fruitfulness of a multidimensional approach in the academic debate on rescaling and planning; empirically, by providing original and updated data on rescaling processes in Italy; and from an applied point of view, by proposing new analytical tools for municipal rescaling and planning that may be employed by European local administrators in different contexts.
Keywords: Raumordnung; Raumwissenschaft; Planungstheorie; Kapazitätsplanung; Indikator; Bewertung; Kommunalplanung; Daseinsvorsorge; Gleichwertigkeit